Change in Total Electron Content During the 26 December 2019 Solar Eclipse: Constraints From GNSS Observations and Comparison With SAMI3 Model Results. Issue 10 (3rd October 2020) - Senapati, Batakrushna; Huba, J. D.; Kundu, Bhaskar; Gahalaut, Vineet K.; Panda, Dibyashakti; Mondal, Saroj Kumar; Catherine, Joshi K.
Abstract: We report spatiotemporal variation in the total electron content (TEC) in ionosphere caused by the 26 December 2019 annular solar eclipse, seen over most of the Southeast Asia. Sparsely distributed network of the Global Navigation Satellite System (GNSS) sites located on the continental parts and on islands documented the transhemispheric coellipse changes in the ionospheric electron density. A significant depletion in TEC of 6–8 TECU (1 TECU = 1 × 10 16 electrons m −2 ) is observed along the path of the eclipse shadow. Simulations using the SAMI3 model are consistent with the observations of TEC depletion. The model also predicted a magnetically conjugate region of marginal increased TEC of 0.2–0.3 TECU around northern Japan and adjacent Pacific Ocean, which is also consistent with the ground‐based GNSS observations in that region. Key Points: GNSS observations during the 26 December 2019 annular solar eclipse show ionospheric TEC depletion of 6–8 TECU TEC enhancement of 0.2–0.3 TECU is observed in the magnetically conjugate region of northern Japan and adjacent Pacific Ocean SAMI3 model predictions are consistent with the TEC depletion along the eclipse shadow and enhancement in the magnetically conjugate region